2015
DOI: 10.1099/ijs.0.000251
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia stagnalis sp. nov. and Burkholderia territorii sp. nov., two novel Burkholderia cepacia complex species from environmental and human sources

Abstract: Nine Burkholderia cepacia complex (Bcc) bacteria were isolated during environmental surveys for the ecological niche of Burkholderia pseudomallei, the aetiological agent of melioidosis, in the Northern Territory of Australia. They represented two multi-locus sequence analysis-based clusters, referred to as Bcc B and Boo L. Three additional environmental and clinical Bcc B isolates were identified upon deposition of the sequences in the PubMLST database. Analysis of the concatenated nucleotide sequence divergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(89 citation statements)
references
References 24 publications
0
83
0
6
Order By: Relevance
“…In the last few years, the taxonomy of the Bcc has evolved significantly, with the description of novel species (Yabuuchi et al, 2000;Coenye et al, 2001;Vandamme et al, 2002;Vermis et al, 2002Vermis et al, , 2004LiPuma, 2005;Vanlaere et al, 2008Vanlaere et al, , 2009Peeters et al, 2013;Smet et al, 2015). Multicenter studies conducted up to 2009 revealed the existence of several clusters of isolates that do not group with the Bcc species described at the time.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, the taxonomy of the Bcc has evolved significantly, with the description of novel species (Yabuuchi et al, 2000;Coenye et al, 2001;Vandamme et al, 2002;Vermis et al, 2002Vermis et al, , 2004LiPuma, 2005;Vanlaere et al, 2008Vanlaere et al, , 2009Peeters et al, 2013;Smet et al, 2015). Multicenter studies conducted up to 2009 revealed the existence of several clusters of isolates that do not group with the Bcc species described at the time.…”
Section: Introductionmentioning
confidence: 99%
“…In the period between the effective and valid publications of these species names, 16 novel species of the genus Burkholderia were described. The 16S rRNA gene sequences of two of them, Burkholderia stagnalis and Burkholderia territorii, are most similar to the 16S rRNA gene sequence of Burkholderia glumae, and the nearest neighbours of these novel species in a phylogenetic tree based on concatenated sequences of seven housekeeping gene fragments are Burkholderia ubonensis and Burkholderia latens (De Smet et al, 2015). However, analysis of the taxonomic positions of the other 14 species shows that they need to be reconsidered in accordance with the reclassification of species of the genus Burkholderia proposed by Sawana et al (2014).…”
mentioning
confidence: 99%
“…In particular, the bronchopulmonary epithelium is covered with a hyperviscous mucus, which impairs mucociliary clearance and favours bacterial colonization and infection. Of the 20 species that currently make up the BCC (Mahenthiralingam et al, 2000;Coenye et al, 2003;Peeters et al, 2013;De Smet et al, 2015), all can cause CF infection, with B. cenocepacia being an important CF pathogen, generally more aggressive than other BCC species. When BCC infects CF patients, the clinical outcome is uncertain, with some patients being colonized for years before showing adverse symptoms and others quickly experiencing diminished respiratory capacity and dying of 'cepacia syndrome' (Govan & Deretic, 1996).…”
Section: Introductionmentioning
confidence: 99%